Prevalence of epiretinal membrane in the phakic eyes based on spectral-domain optical coherence tomography - Kim, Boyun (PLoS One, 2021)
The prevalence of epiretinal membrane (ERM) and associated factors in the phakic eyes have not been fully elucidated yet. This cross-sectional study included 2,354 phakic eyes without retinal diseases or surgical history. Ocular parameters, such as uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), spherical equivalent (SE), intraocular pressure (IOP), white-to-white corneal diameter (WTW), mean keratometric value (Km) of total corneal refractive power at 4-mm diameter (TCRP4), astigmatism of TCRP4, total corneal irregular astigmatism (TCIA), pupil diameter, axial length (AXL), anterior chamber depth (ACD), lens thickness (LT), and posterior vitreous detachment (PVD) were compared between ERM group and control group. Additionally, an age-matched control group was selected by individual matching and compared with the ERM group to eliminate the confounders. Multiple logistic regression analysis was performed to evaluate the factors associated with the presence of ERM. Among 2,354 eyes, 429 eyes (18.2%) had ERM based on spectral-domain optical coherence tomography. The ERM group showed higher prevalence of PVD, worse CDVA, higher astigmatism of TCRP4, higher TCIA, smaller pupil size, longer AXL, and thicker LT than control group (P < 0.001, P < 0.001, P = 0.011, P < 0.001, P = 0.023, P < 0.001, and P < 0.001, respectively). Only PVD, CDVA, SE, astigmatism of TCRP4, TCIA, and AXL maintained the significance when compared with the age-matched control group (P < 0.001, P = 0.026, P < 0.001, P = 0.001, P = 0.003, and P < 0.001, respectively). Multivariate logistic regression analysis showed that age, PVD, CDVA, and TCIA were independently associated with the presence of ERM (P < 0.001, P < 0.001, P = 0.011, and P = 0.002). The prevalence of ERM detected using SD-OCT was 18.2% in the middle aged phakic population. Eyes with TCIA, in addition to older age and PVD, were more likely to have ERM.